A study on the correlation between professional self-concept, social support and presenteeism among nurses - Li, Danqin; Liu, Xiaowei; Huang, Shaojuan; Zeng, Yiyun; Lu, Jinsheng (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to investigate the relationships between nurses' professional self-concept, social support, and presenteeism, providing insights for optimizing nursing human resource management.MethodsA cross-sectional survey was conducted using the professional self-concept scale, social support rating scale, and presenteeism scale among 520 nurses from tertiary hospitals in Guangdong Province, China. Descriptive statistics, Pearson correlation analysis, and hierarchical multiple linear regression were employed for data analysis.ResultsA total of 503 valid questionnaires were collected, yielding an effective response rate of 96.73%. There was a significant negative correlation between professional self-concept and presenteeism [r = −0.339, 95%CI (−0.414, −0.259), P < 0.05]. There was also a significant negative correlation between social support and presenteeism [r = −0.292, 95%CI (−0.370, −0.209), P < 0.05]. Hierarchical multiple regression analysis showed that in Model 1, surgery, operating room, and work intensity evaluation of “relatively high” and “moderate” had obvious predictive effects on presenteeism (P < 0.05). In Model 2, surgery, work intensity evaluation of “relatively high” and “moderate”, and professional self-concept had obvious predictive effects on presenteeism (P < 0.01). In Model 3, surgery, operating room, work intensity evaluation of “relatively high” and “moderate”, professional self-concept, and social support had obvious predictive effects on presenteeism (P < 0.05). The R2 of Model 1, Model 2, and Model 3 were 6.6%, 16.1%, and 17.4% respectively. The results of the mediation effects test showed that perceived social support partially mediated the relationship between professional self-concept and presenteeism.ConclusionEnhancing nurses' professional self-identity and strengthening social support may be predictive of lower levels of presenteeism, potentially contributing to improved nursing team performance and patient safety.